Evaluation and monitoring of established rheumatoid arthritis. Issue 5 (October 2019) - Castrejon, Isabel
Abstract: Established rheumatoid arthritis (RA) is a term used to distinguish patients with longer disease duration versus early RA or undifferentiated arthritis that may progress to RA. Although, there is no uniform definition for early disease, a cut-off of 2 years is used in most clinical trials and observational studies. In the evaluation of established RA, clinicians should incorporate a comprehensive set of measures addressing: (1) disease activity, especially inflammation that may benefit of intensification of therapy, (2) health status, (3) comorbidities, and (4) damage. Ideally, measures should include the patient and physician perspectives and be feasible, reliable, valid and sensitive to change. Traditionally, measures have been incorporated in clinical research, but it would be worthwhile to integrate them into routine care. Data collection systems adapted to rheumatologists needs, could advance care for individual patients and facilitate large observational studies to evaluate interventions for the whole spectrum of RA.